Legal Analysis of Copyright of a Book Work Against Duplication through Photocopying - Khalid, Hasbuddin (Universitas Islam Lamongan, 2023)
AbstractThe aim of the research is to find out and analyze the duplication of a book's copyrighted work with a photocopy which is contrary to the provisions of Law Number 28 of 2014 concerning Copyright. The effort to overcome this is by law enforcement in order to obtain legal protection for book copyright holders, therefore the enforcer The law must always coordinate with publishers, including elements of the Director General of Intellectual Property Rights, Department of Law and Human Rights, book publishers, even bookstores and even by involving the public so as not to give room to people who seek to profit from other people's work.Â